S131 Fatigue in bronchiectasis: its relationship to pseudomonas colonisation, dyspnoea and airflow obstruction. (16th November 2010) - Macfarlane, J G; Tedd, H; McAlinden, P; Small, T; Rostron, L; Newton, J; De Soyza, A
Abstract : Introduction and objectives: Fatigue is a complex and disabling symptom in non-CF bronchiectasis (nCF-Br) and can be formally measured using the Fatigue Impact Scale (FIS). FIS scores of >40 out of 120 are clinically significant. The FIS score has been shown to be prognostic of premature death in Primary Biliary cirrhosis but is not linked to markers of organ dysfunction (liver function tests). As poorer outcomes have been recently reported in Pseudomonas infected nCF-Br patients we aimed to measure the correlation between FIS scores and parameters of severity in nCF-Br, for example, Pseudomonas infection, degree of dyspnoea and airflow obstruction. Methods: FEV1 % predicted, MMRC dyspnoea score (MMRCD) and FIS were recorded in stable adult nCF-Br patients attending specialist clinic. All previous sputum cultures isolating Pseudomonas aeruginosa were reviewed. Two groups of patients were studied: those with Pseudomonas 'colonisation' (organism cultured ≥2 occasions, 3 months apart within 1-year period) and those with 'isolation' (organism cultured ≥1 occasion). Statistical comparison used χ 2, Fisher's correlation and Mann–Whitney U tests. Results: 73F, 41M patients were included; average age 60 (range 24–90) with an average FEV1 66% predicted (SD +/−26%). 54 (47%) patients had Pseudomonas isolation; 38 (33%) patients had colonisation. Fatigue levels were similar in patients with and without colonisation (median 48.5 vs 36.5, p=0.31). Significant fatigue (FIS>40) was more common in patients with Pseudomonas isolation (47%) than those with no previous isolates (p=0.04, OR=2.2) However, fatigue levels, although increased, were not significantly different (median FIS 50 vs 32; p=0.064). Fatigue correlated with MMRCD (r=0.54, p<0.0001) but less well with FEV1 % predicted (r=0.2, p=0.04). FEV1 % predicted was lower in patients with Pseudomonas colonisation (median FEV1 49% vs 74%, p=0.0007) and in patients with Pseudomonas isolation (median FEV1 52% vs 74%, p=0.002). Conclusions: Pseudomonas infection (past or present) appears to be associated with greater clinically significant fatigue scores and poorer lung function. Fatigue doesn't strongly correlate with FEV1 % predicted but is correlated with MMRCD. Further regression analysis of variables is underway to understand these inter relationships further. Systemic aspects of Pseudomonas infection may be different to other infections explaining the divergence.